Diazirines as Potential Molecular Imaging Tags: Probing the Requirements for Efficient and Long‐Lived SABRE‐Induced Hyperpolarization. Issue 40 (24th July 2017) - Shen, Kun; Logan, Angus W. J.; Colell, Johannes F. P.; Bae, Junu; Ortiz, Gerardo X.; Theis, Thomas; Warren, Warren S.; Malcolmson, Steven J.; Wang, Qiu
Abstract: Diazirines are an attractive class of potential molecular tags for magnetic resonance imaging owing to their biocompatibility and ease of incorporation into a large variety of molecules. As recently reported, 15 N2 ‐diazirine can be hyperpolarized by the SABRE‐SHEATH method, sustaining both singlet and magnetization states, thus offering a path to long‐lived polarization storage. Herein, we show the generality of this approach by illustrating that the diazirine tag alone is sufficient for achieving excellent signal enhancements with long‐lasting polarization. Our investigations reveal the critical role of Lewis basic additives, including water, on achieving SABRE‐promoted hyperpolarization. The application of this strategy to a 15 N2 ‐diazirine‐containing choline derivative demonstrates the potential of 15 N2 ‐diazirines as molecular imaging tags for biomedical applications. Abstract : Tag team : 15 N2 ‐diazirine motifs are demonstrated to be capable of supporting long‐lasting polarization by the experimentally simple and cost‐effective hyperpolarization method of SABRE‐SHEATH, presenting promising potential as molecular tags for NMR/MRI imaging.